The use of supplementary materials in EFL classes: A comparative analysis of public and private high schools - Borrero Peralta, María Ximena (2012)
This research is about the use of supplementary materials in EFL classes with a comparative analysis between public and private high schools. The purpose of this study is to determine and analyze supporting materials used in EFL public and private high schools and to compare their use in both schools; in order to accomplish this goal, this research was applied to students from first, second and third years of senior high schools in the city of Cuenca. A qualitative analysis was applied to find out if the quality of the materials was good, if they were pertinent to the class´ objective and appropriate to the students´ needs, age and level of English. On the other hand, a quantitative analysis was done to measure the frequency of use of these materials in each year and they were compared between both schools to find out where they use more materials. This research demonstrates that teachers use supplementary materials in their classes in both schools. However, from all the supplementary materials available only a few materials are used way these students the language.